Digital Marketing Strategy in Enhancing Brand Awareness and Profitability of E-Commerce Companies - Eloise Rose, Dhiyah; Van Der Merwe, John; Jones, Jack (APTISI Transactions on Management (ATM), 2024)
Digital marketing has become a critical aspect in the marketing strategy of e- commerce companies in the current digital era. This research aims to investigate the impact of digital marketing on brand awareness and profitability of e- commerce companies. A quantitative research approach was employed by collecting data from 100 respondents consisting of marketing managers and executives of e-commerce companies. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The findings suggest that effective digital marketing strategies can enhance brand awareness and profitability. Consequently, managers can allocate resources more wisely and achieve competitive advantage. In the context of increasingly intense market competition, this understanding is crucial. This research contributes to the literature on digital marketing within the realm of e-commerce.